Attention-Deficit/Hyperactivity Disorder and Delayed Sleep Phase Syndrome in Adults: A Randomized Clinical Trial on the Effects of Chronotherapy on Sleep. Issue 6 (December 2022) - van Andel, Emma; Bijlenga, Denise; Vogel, Suzan W. N.; Beekman, Aartjan T. F.; Kooij, J. J. Sandra
Delayed sleep phase syndrome (DSPS) is the most common sleep disturbance in adults with attention-deficit/hyperactivity disorder (ADHD). We previously showed that chronotherapy with melatonin effectively advanced the dim-light melatonin onset (DLMO), a biomarker for the internal circadian rhythm, by 1.5 h and reduced ADHD symptoms by 14%. Melatonin combined with bright light therapy (BLT) advanced the DLMO by 2 h, but did not affect ADHD symptoms. This article explores whether sleep times advanced along with DLMO, leading to longer sleep duration and better sleep in general, which might explain the working mechanism behind the reduction in ADHD symptoms after treatment with melatonin. This article presents exploratory secondary analysis on objective and self-reported sleep characteristics from a three-armed double-blind randomized placebo-controlled clinical trial (RCT), which included 49 adults (18-55 years) with ADHD and DSPS. Participants were randomized to receive sleep education and 3 weeks of (1) 0.5 mg/day placebo, (2) 0.5 mg/day melatonin, or (3) 0.5 mg/day melatonin plus 30 min of bright light therapy (BLT) between 0700 and 0800 h. Sleep was assessed at baseline, directly after treatment, and 2 weeks after the end of treatment. Objective measures were obtained by actigraphy, self-reported measures by various sleep questionnaires and a sleep diary. Melatonin with or without BLT did not advance sleep times, improve sleep in general, or strengthen wake-activity rhythms. So even though the DLMO had advanced, sleep timing did not follow. Adding extensive behavioral coaching to chronotherapy is necessary for advancing sleep times along with DLMO and to further alleviate ADHD symptoms.